2020
DOI: 10.2169/internalmedicine.5132-20
|View full text |Cite
|
Sign up to set email alerts
|

Serum Anti-<i>Helicobacter pylori</i> IgG Antibody Titer in <i>H. pylori</i>-negative Cases with a Different Gastric Mucosal Atrophy Status

Abstract: Objective This retrospective study was performed to investigate the anti- Helicobacter pylori IgG antibody serum titers in H. pylori -negative subjects with different degrees of gastric mucosal atrophy including C0 grade atrophy. Methods The absence of H. pylori infection was determined based on both negative serum anti- H. pylori IgG antibody test findings and no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Serum anti‐ H. pylori IgG antibody detection was performed with a SphereLight H. pylori antibody J kit, and the antibody titer was automatically determined using a chemiluminescent enzyme immunoassay method, with a value ≥ 4.0 U/ml defined as positive, according to the manufacturer's instructions. 7 , 8 , 9 In addition, a precise medical history concerning the status of H. pylori infection (negative, positive, post‐eradication) was obtained in an interview with the subject conducted by a public health nurse. Usage of a proton pump inhibitor or H2 receptor antagonist (H2RA) within the preceding 3 months was also determined at the time of the interview, although details related to duration or dosage of anti‐secretory drugs were not obtained for this study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Serum anti‐ H. pylori IgG antibody detection was performed with a SphereLight H. pylori antibody J kit, and the antibody titer was automatically determined using a chemiluminescent enzyme immunoassay method, with a value ≥ 4.0 U/ml defined as positive, according to the manufacturer's instructions. 7 , 8 , 9 In addition, a precise medical history concerning the status of H. pylori infection (negative, positive, post‐eradication) was obtained in an interview with the subject conducted by a public health nurse. Usage of a proton pump inhibitor or H2 receptor antagonist (H2RA) within the preceding 3 months was also determined at the time of the interview, although details related to duration or dosage of anti‐secretory drugs were not obtained for this study.…”
Section: Methodsmentioning
confidence: 99%
“…Those with a history of gastric surgery or whose status of H. pylori infection could not be determined based on medical records and/or serum antibody test findings were excluded from enrollment. Serum anti‐ H. pylori IgG antibody detection was performed with a SphereLight H. pylori antibody J kit, and the antibody titer was automatically determined using a chemiluminescent enzyme immunoassay method, with a value ≥ 4.0 U/ml defined as positive, according to the manufacturer's instructions 7–9 . In addition, a precise medical history concerning the status of H. pylori infection (negative, positive, post‐eradication) was obtained in an interview with the subject conducted by a public health nurse.…”
Section: Methodsmentioning
confidence: 99%
“…AG and IM are considered pre-neoplastic gastric lesions, but studies have observed that H. pylori infection status can spontaneously become negative in advanced AG [37, 38]. Plausible explanations include the unintentional eradication when treating another infection, the spontaneous disappearance of H. pylori due to severe mucosal atrophy and IM [39, 40], and the effects of the accompanying microbiota in H. pylori -infected individuals [41].…”
Section: Discussionmentioning
confidence: 99%
“…4.0 U/mL defined as positive, according to the manufacturer's instructions. Several investigators previously demonstrated the usefulness of these kits (15)(16)(17)(18). At our institution, when eradication therapy is not confirmed to be successful, it is recommended that patients undergo an H. pylori stool antigen test.…”
Section: Methodsmentioning
confidence: 99%
“…When GMA was endoscopically observed, the degree was evaluated using the classification of Kimura and Takemoto, in which GMA is classified into six grades (C1, C2, C3, O1, O2, O3) (22). Cases without GMA were determined to be C0 for this study (16), so the classification of GMA was divided into seven groups (C0 and the grades noted above).…”
Section: Methodsmentioning
confidence: 99%